Seronegative antibody‐mediated neurology after immune checkpoint inhibitors - Wilson, R; Menassa, D; Davies, A; Michael, S; Hester, J; Kuker, W; Collins, G; Cossins, J; Beeson, D; Steven, N; Maddison, P; Rinaldi, S; et al. (Wiley, 2018)
Checkpoint inhibitor medications have revolutionized oncology practice, but frequently induce immune‐related adverse events. During autoimmune neurology practice over 20 months, we prospectively identified four patients with likely antibody‐mediated neurological diseases after checkpoint inhibitors: longitudinally extensive transverse myelitis, Guillain–Barré syndrome, and myasthenia gravis. All patients shared three characteristics: symptoms commenced 4 weeks after drug administration, responses to conventional immunotherapies were excellent, and autoantibodies traditionally associated with their syndrome were absent. However, serum immunoglobulins from the myelitis and Guillain–Barré syndrome patients showed novel patterns of tissue reactivity. Vigilance is required for antibody‐mediated neurology after checkpoint inhibitor administration. This phenomenon may inform the immunobiology of antibody‐mediated diseases.